CONTROL OF MANUFACTURING OVERHEAD COSTS IN PRODUCT COSTING - Andre Saputra Hutajulu; Adisti Amalia; Ernita Ernita; Raujatul Jannah; Rozatul Zahara; Wirzi Karisa; Mariana Mariana (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2026)
The control of manufacturing overhead costs is a critical challenge in determining accurate product costs. This systematic literature review analyzes 17 selected articles to examine the effectiveness of costing methods, the influence of firm characteristics, and the methodological profile of research in this field. The findings indicate that Activity-Based Costing (ABC) consistently outperforms traditional systems in providing accurate overhead cost allocation and relevant information for strategic decision-making. The success of implementing such systems heavily depends on firm contingency factors, with product mix complexity and availability of organizational resources emerging as key determinants. Methodologically, existing research is still dominated by qualitative approaches and case studies, highlighting the need for more inferential quantitative research to strengthen external validity and the generalizability of findings. The implications of this research emphasize the necessity of aligning costing systems with specific firm contexts and encourage the development of further studies with mixed-methods designs to address the complexities of overhead cost control in the modern manufacturing era.